2008
DOI: 10.1021/jp0766499
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxygen Coverage at Pt−Fe Alloy Cathode for the Enhanced Oxygen Reduction Reaction Studied by EC−XPS

Abstract: Direct observation of adsorbed species relating to the oxygen reduction reaction (ORR) on cathode catalyst surfaces is very important for an elucidation of the ORR and finding a clue of higher-performance catalysts for polymer electrolyte fuel cells. We first identified quantitatively oxygen-containing species adsorbed on electrodes of pure Pt and a Pt skin layer formed on a Pt−Fe alloy surface in N2- and O2-saturated 0.1 M HF solution by X-ray photoelectron spectroscopy combined with an electrochemical cell (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
188
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 179 publications
(200 citation statements)
references
References 36 publications
8
188
2
2
Order By: Relevance
“…[22][23][24][25][26][27][28][29] For example, the values of j k for Pt-Co alloys showed a maximum at the atomic ratio of Pt/Co = 3. 4,5,14 It has been reported that the electronic structure of the Pt skin layer formed on Pt-M alloys could change with the composition of the underlying alloy, reaching a maximum at the optimum alloy composition or alloying metal species M. 24,[30][31][32] Because the surface is not perfectly covered with uniform Pt skin layer, j k often decreases appreciably by dealloying of M during the operation of PEFCs or electrochemical measurements in acidic electrolyte solutions, particularly at higher temperatures. 14,33 Here, we focus on the influence of crystal structure (ordered and disordered structures) of Pt 3 Co alloy nanoparticles on the ORR activity and durability.…”
mentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] For example, the values of j k for Pt-Co alloys showed a maximum at the atomic ratio of Pt/Co = 3. 4,5,14 It has been reported that the electronic structure of the Pt skin layer formed on Pt-M alloys could change with the composition of the underlying alloy, reaching a maximum at the optimum alloy composition or alloying metal species M. 24,[30][31][32] Because the surface is not perfectly covered with uniform Pt skin layer, j k often decreases appreciably by dealloying of M during the operation of PEFCs or electrochemical measurements in acidic electrolyte solutions, particularly at higher temperatures. 14,33 Here, we focus on the influence of crystal structure (ordered and disordered structures) of Pt 3 Co alloy nanoparticles on the ORR activity and durability.…”
mentioning
confidence: 99%
“…Wakisaka et al indicated that not only the OH ad but also atomic oxygen (O ad ) of two electron units is adsorbed at 1.0 V in O 2 -saturated 0.1 M HF solution. 38 The calculated Pt oxide coverage of 0.4 was obtained at low humidity of the CL with the ionomer, and that condition seemed to decrease the amount of exposed metallic Pt due to adsorption of the anionic groups of the ionomer, i.e., sulfonate. 39 However, we consider that the adsorbed anions can be desorbed by the effect of generated H 2 O by the ORR (Equation 4) during step 3.…”
Section: Resultsmentioning
confidence: 93%
“…114 By EC-XPS technique, we have, for the first time, quantitatively identified oxygen-containing species (O ad , OH ad , and H 2 O ad ) on Pt skin/Pt alloys in N 2 -and O 2 -saturated 0.1 M HF solution. [2][3][4]6 The values of coverage of OH ad , ª[OH ad ], on Pt-skin/Pt alloys and purePt were at nearly the same level. This is completely inconsistent with the common view that the enhancement in the ORR activity on Pt alloys is due to a mitigation of blocking or "poisoning" of the surface by decreasing ª[OH ad ] or coverage of O ad , ª[O ad ].…”
Section: Mechanism Of Enhanced Orr Activities At Pt Skin Layersmentioning
confidence: 94%
“…[1][2][3][4] For PEFC anode and cathode catalysts, the activity and its degradation have been analyzed by multilateral techniques such as X-ray photoelectron spectroscopy combined with an electrochemical cell (EC-XPS), 2,[5][6][7][8] in situ Fourier-transform infrared spectroscopy (FTIR), [9][10][11][12][13][14][15][16][17][18][19][20][21][22] electrochemical quartz crystal microbalance (EQCM), [23][24][25][26] in situ scanning tunneling microscopy (STM), [27][28][29][30][31] in addition to conventional electrochemical measurements such as rotating disk electrode (RDE), [32][33][34] channel flow electrode (CFE), 21,35,36 and channel flow double electrode (CFDE) methods. [37][38][39][40][41][42] Based on these results, new practical catalysts have been synthesized.…”
Section: Introductionmentioning
confidence: 99%